(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The main objective of this work is to study the mathematical modeling of the adsorption of Co2+ ions on sugarcane bagasse (SCB) for approximate the nature of the adsorption. The together of results obtained show that the adsorption process is favorable for a chemisorption and monolayer. Also, the adsorption process is expressed by the second order kinetic law. Thus the negative values of ΔG° and the positive values of ΔH° opt for an endothermic and spontaneous process. Also, the positive values of ΔS° indicate the increase in the randomness at the solid / liquid interface during the adsorption of the Co2+ metal ions.